The Relationship Between Social Media Communication and Word of Mouth Inside Brand Image and Purchase Intention - Melani Widyawati Sidharta; Tantri Yanuar Rahmat Syah; Agusdini Banun Saptaningsih (Journal of Multidisciplinary Academic, 2021)
Purchase intention is one of the most significant aspect that influences the advancement of a business also used as a consumer behaviour prediction. Traditional marketing is one of abandoned and digital marketing became a trend with its virtual and real time features which is allowed the company to directly communicate with their consumer. Thus, this study aimed to observe the impact of social media communication and word of mouth in the brand image and purchase intention. The participant of this study is obtained by purposive sampling with the method of cross-sectional survey. The result shows a structural model-Listrel from 200 participants show that social media communication with user generated content and firm generated content, also word of mouth, directly influences brand image and purchase intention. Here, Brand image partially mediates the relationship between social media communication with user and firm generated content (T-value 2.28 to 5.24), word of mouth with purchase intention (T-value 2.50). This research suggests that firm management need to strategically regulate social media marketing to obtain maximum result.